Coaching and mentoring for academic development - Guccione, Kay; Hutchinson, Steve (Surviving and thriving in academia, 2021)
Learning through dialogue brings a powerful opportunity for individuals to connect to colleagues, navigate professional demands, and meet the challenges posed by a turbulent world. Written for all who mentor or coach in universities, this book addresses a critical question: how can mentoring and coaching conversations be effective and accessible ways to support researcher and academic development? Drawing on their wide range of experiences of coaching and mentoring, and designing and leading institutional programmes and policy, Guccione and Hutchinson provide an insight into the founding principles of reflective ethical practice, as well as a pragmatic and easy to navigate toolkit supporting you to understand the needs of the people you want to develop. Including bite-sized chapters packed full of applied solutions, the authors help you to design, re-design, or troubleshoot your mentoring or coaching approach, and offer up go-to guidance for building and enhancing a culture of developmental dialogue at the individual, programme and organisational level.